Pengaruh Video Animasi terhadap Pengetahuan dan Sikap Siswa Sekolah Dasar tentang Diare di Kabupaten Tulungagung - Al Zunan Nurbakti; Dimas Dwi Yoga Saputra; Wandi Wandi; Fiashriel Lundy (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Diarrhea remains a serious health problem in Indonesia, especially among primary school children. Riskesdas 2018 recorded a prevalence of 6.2% in children aged 5-14 years. Cases in Tulungagung reached 15,639 in 2018, and at the Kedungwaru Health Center, diarrhea ranked sixth with 16 cases in Januari 2025. It highlights the importance of prevention through effective health education, such as with animated videos. Knowing the influence of health education using animated video media on increasing students' knowledge and attitudes about diarrhea prevention at Primary School. This study is a pre-experimental quantitative study with a one group pretest-posttest design. The sample consisted of 37 students in grades 4 and 5 who were taken with the total sampling technique. Knowledge and attitude data were measured using questionnaires and analyzed with the Wilcoxon Signed Rank Test. There was an increase in knowledge from an average of 71.86 to 92.00 (p = 0.000) and an increase in attitude from 47.11 to 54.57 (p = 0.000). Increased knowledge from 54% in the category to 97.3% in the good category. Positive attitudes increased from 56.8% to 75.7%. Health education using animated video media has been shown to be effective in increasing the knowledge and attitudes of elementary school students in the prevention of diarrhea